Opioids for Relief of Dyspnea Immediately Before Death in Patients With Noncancer Disease: A Case Series Study. (August 2019) - Murakami, Maki
Background: Dyspnea is commonly found in most conditions among patients with progressive noncancer disease. Objective: To clarify the effectiveness and safety of opioid administration for the treatment of dyspnea immediately before death in patients with noncancer disease. Methods: A retrospective case-series study involving 13 consecutive terminally ill patients who were near death and diagnosed with noncancer disease, and had refractory dyspnea and received opioid therapy, was performed. The authors investigated the route of administration, period, dosage of opioids, intensity of dyspnea—scored according to the Japanese version of the Support Team Assessment Schedule—and clinical course from a review of medical records. Results: The mean age of the patients was 86.5 ± 7.6years (range: 72-98years). The primary causes of dyspnea that led to opioid administration were heart failure (n = 10) and respiratory failure (n = 3). Oxycodone was used in one patient who experienced a complication of chronic renal failure; morphine was used in the other 12 patients. The route of opioid administration was continuous infusions in 11 patients, suppository in one, and oral administration in one. The final dose of oral morphine equivalents was 20.1 ± 8.1 mg/d (range: 5-36 mg [median: 18 mg]). All patients improved in symptom score after opioid administration. The score was significantly decreased from 3.2 ± 0.7 at the beginning of opioid administration to 1.2 ± 0.6 at final estimation ( P < .001). No severe adverse events occurred. Conclusions: Low-dose opioid administration in patients with terminally ill noncancer improved dyspnea and occurred no severe adverse events.